Climate Change and Transboundary Waters: A Study of Discourse in the Mekong River Commission. (September 2014) - Gerlak, Andrea K.; Schmeier, Susanne
In our study of climate change discourse in the Mekong River Commission (MRC) over the past decade, we find that climate change policy strategies are framed as science-based actions. Scale is largely expressed in terms of short-term, immediate temporal horizons that are human-dominated and regionally based. Further, we uncover a broadening of climate change discourse across multiple scales to incorporate justice, integrated water resource management (IWRM), development, and security frames. These patterns not only reflect trends in the larger global water governance and climate change discourse and reinforce historic patterns in the Mekong River Basin, but they also signal more strategic efforts by the MRC and member states to attract donor support. In our examination of links between discourse and MRC climate change action, we argue that the MRC's climate change actions narrowly reflect the production of studies and project scoping rather than real adaptive actions in the basin. We examine official documents of the MRC over the past decade to better understand how the discourse around climate change is framed and to what extent the discourse is linked to climate change actions.